In pursuit of comparable concepts and data about collective action - Poteete, Amy; Ostrom, Elinor (International Food Policy Research Institute, 2003)
Research on collective action confronts two major obstacles. First, inconsistency in the conceptualization and operationalization of collective action, the key factors expected to affect collective action, and the outcomes of collective action hampers the accumulation of knowledge. Inconsistent terminology obscures consistent patterns. Second, the scarcity of comparable data thwarts evaluation of the relative importance of the many variables identified in the literature as likely to influence collective action. The International Forestry Resources and Institutions (IFRI) research program addresses both of these problems. Since its founding in 1993, the IFRI network of collaborating research centers has used a common set of methods and concepts to study forests, the people who use forest resources, and their institutions for resource management. The basic social unit of analysis in IFRI is the user group, defined as a set of individuals with the same rights and responsibilities to forest resources. This definition does not require formal organization or collective action, since these features are potential dependent variables. This strategy for data collection allows analysis of relationships between diverse forms of social heterogeneity and collective action within groups with comparable rights to resources. IFRI's relational database also captures the connections among forest systems, sets of resource users, particular forest products, formal and informal rules for resource use, and formal local and supra-local organizations. By the middle of 2001, the IFRI database included data on 141 sites with 231 forests, 233 user groups, 94 forest organizations, and 486 products in 12 countries. Drawing upon these data, IFRI researchers are contributing substantially to our understanding of collective action for institutional development, the mediating role institutions play relative to demographic and market pressures in patterns of resource use, and relationships between particular institutions and forest conditions. The paper describes IFRI's strategy for collecting comparable data based on consistent conceptualization and operationalization, summarizes the contributions of IFRI research to the study of collective action for natural resource management, and identifies continuing challenges.